2016
DOI: 10.5194/hess-20-3013-2016
|View full text |Cite
|
Sign up to set email alerts
|

Vegetative impacts upon bedload transport capacity and channel stability for differing alluvial planforms in the Yellow River source zone

Abstract: Abstract. The influence of vegetation upon bedload transport and channel morphodynamics is examined along a channel stability gradient ranging from meandering to anabranching to anabranching-braided to fully braided planform conditions along trunk and tributary reaches of the Upper Yellow River in western China. Although the regional geology and climate are relatively consistent across the study area, there is a distinct gradient in the presence and abundance of riparian vegetation for these reaches atop the Q… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…Riparian vegetation area increases the river resistance and effectively reduces the flow velocity [1], greatly reducing the sediment carrying capacity [2], thus affecting the sediment transport and deposition process [3,4] and final river bed morphology. The flow tends to shift to the main channel with minimal resistance [5], increasing channel brush depth and reducing the channel curvature, straightening the meandering channels [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Riparian vegetation area increases the river resistance and effectively reduces the flow velocity [1], greatly reducing the sediment carrying capacity [2], thus affecting the sediment transport and deposition process [3,4] and final river bed morphology. The flow tends to shift to the main channel with minimal resistance [5], increasing channel brush depth and reducing the channel curvature, straightening the meandering channels [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…China's recently formed Sanjiangyuan National Nature Reserve, for example, foregrounds the ecological values of the Qinghai-Tibetan Plateau (see Li et al, 2012). While reports of controls on river morphology have emphasised the role of temperature gradients in controlling vegetationstream responses on the Plateau (Li et al, 2016;Yu et al, 2014), these relationships exist in a context of up to 8800 years of grazing by nomadic Tibetan herders (Miehe et al, 2008(Miehe et al, , 2009. A focus on conserving the region's naturalness, made explicit in the reserve's name, along with concerns for soil loss and river sedimentation, drove efforts to concentrate herders into fixed settlements after grassland degradation was linked to changes in pastoral regime (Xin, 2008).…”
Section: Which Nature?mentioning
confidence: 99%
“…The results of the physical model experiment showed that a substantial reduction in the flood frequency of the river flow after dam construction caused the river to gradually develop from meandering to straight [33]. In addition to water and sediment conditions, vegetation is also considered an important factor affecting sediment transport and the morphological development of river channels [34,35]. The latter has also been noted to promote meandering and alter the meander scale in numerical simulations of river meandering.…”
Section: Introductionmentioning
confidence: 99%